Identifying the greatest earthquakes of the past 2000 years at the Nehalem River estuary, northern Oregon coast, USA - Nelson, Alan R. (2020)
We infer a history of three great megathrust earthquakes during the past 2000 years at the Nehalem River estuary based on the lateral extent of sharp (≤3 mm) peat-mud stratigraphic contacts in cores and outcrops, coseismic subsidence as interpreted from fossil diatom assemblages and reconstructed with foraminiferal assemblages using a Bayesian transfer function, and regional correlation of 14C-modeled ages for the times of subsidence. A subsidence contact from 1700 CE (contact A), sometimes overlain by tsunami-deposited sand, can be traced over distances of 7 km. Contacts B and D, which record subsidence during two earlier megathrust earthquakes, are much less extensive but are traced across a 700-m by 270-m tidal marsh. Although some other Cascadia studies report evidence for an earthquake between contacts B and D, our lack of extensive evidence for such an earthquake may result from the complexities of preserving identifiable evidence of it in the rapidly shifting shoreline environments of the lower river and bay. Ages (95% intervals) and subsidence for contacts are: A, 1700 CE (1.1 ± 0.5 m); B, 942–764 cal a BP (0.7 ± 0.4 m and 1.0 m ± 0.4 m); and D, 1568–1361 cal a BP (1.0 m ± 0.4 m). Comparisons of contact subsidence and the degree of overlap of their modeled ages with ages for other Cascadia sites are consistent with megathrust ruptures many hundreds of kilometers long. But these data cannot conclusively distinguish among different types or lengths of ruptures recorded by the three great earthquake contacts at the Nehalem River estuary.